The effectiveness of butterfly pea hydrogel film (Clitoria Ternatea) with chitosan and poly-vinyl-alcohol based as diabetic wound healing - Wicita, Prisca Safriani; Daud, Rizka Puji Astuti; Sapiun, Zulfiayu; Yahya, Cindy; Wantaa, Nurunnisa; Mohamad, Fihrina; Imran, Arlan K.; Hartati, Hartati; Husain, Fadli (Faculty of Pharmacy, Universitas Pancasila, 2024)
Butterfly pea possesses antioxidant activities with IC50 470 μg/ml of wound healing acceleration quality. Hydrogel for diabetic wound healing due to its physical characteristic that binds water, aside from its qualities that wets the surface and bio-compatibility in the body. This study aimed to identify effectivity test of hydrogel film preparation with butterfly pea (clitoria ternatea l.) Water extract for diabetic wound healing, employing true experimental method which involves 12 rats divided into 4 groups. The control group was treated without the Hydrogel (HET) or HET0 on hyperglycemic rats, HET1 (2%), HET2 (5%), and HET3 (7.5%). The findings revealed wounds treated with HET0 was healed in 9 days with 11.13 mm of diameter (100%), HET1 was healed in 6 days with 15.22 mm of diameter (100%), HET2 that was healed in 4 days with 11.29 mm of diameter (100%), and HET3 that was healed in 8 days with 9.05 mm of diameter (100%). It was concluded that the effectivity test revealed that the best formula is HET2 (5%) healed in 4 days with 11.29 mm of diameter in 100%.